2015
DOI: 10.3748/wjg.v21.i35.10159
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and safety of radiofrequency-assisted hepatectomy for hepatocellular carcinoma with cirrhosis: A single-center retrospective cohort study

Abstract: AIM:To assess the efficiency and safety of radiofrequencyassisted hepatectomy in patients with hepatocellular carcinoma (HCC) and cirrhosis. METHODS:From January 2010 to December 2013, 179 patients with HCC and cirrhosis were recruited for this retrospective study. Of these, 100 patients who received radiofrequency-assisted hepatectomy (RF+ group) were compared to 79 patients who had hepatectomy without ablation (RF-group). The primary endpoint was intraoperative blood loss. The secondary endpoints included li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Another issue associated with coagulated-assisted LR is infectious complications. The rate of abdominal abscesses varies from 0% to 9.0% (Table 5) [15][16][17][18][19]31]. In our study, the rate of biliary leakage was 7.1%, and the rate of abdominal abscess was 8.9%.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Another issue associated with coagulated-assisted LR is infectious complications. The rate of abdominal abscesses varies from 0% to 9.0% (Table 5) [15][16][17][18][19]31]. In our study, the rate of biliary leakage was 7.1%, and the rate of abdominal abscess was 8.9%.…”
Section: Discussionmentioning
confidence: 46%
“…We also used this procedure in this study. RF-LR or MW-LR was successfully performed with minimal blood loss and limited Pringle manoeuvre times for cirrhotic patients with HCC in some reports [15][16][17][18][19]31]. In the present study, intraoperative blood loss was reduced to 253 ml.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…As in other studies, the alanine transaminase ALT and aspartate transaminase AST levels were measured postoperatively to assess the extent of hepatic damage to the remnant liver. RFA-assisted hepatectomy patients showed signi cantly higher serum ALT levels than did those undergoing non-RFA-assisted hepatectomy ; moreover, RFA-assisted hepatectomy can further damage the cirrhotic liver 21 . However, the AST and ALT levels quickly improved in the present study, and the lack of PM might have contributed to the absence of severe hepatic damage.…”
Section: Discussionmentioning
confidence: 95%
“…The device is simple, cost effective, facilitates safe and efficient liver resection and fosters the practice of parenchymal sparing liver resections with a significant reduction in bleeding and subsequent perioperative complications [ 46 , 47 ]. To date, several retrospective and prospective (randomized or non-randomized studies) have been reported comparing various techniques of liver resections’ however, a meta-analysis comparing “bloodless technique of liver resection” (Habib™-4X) with the standard clamp-crush (CC) technique is lacking [ 48 , 49 , 50 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%